2016
DOI: 10.21776/ub.ijleg.2016.002.01.7
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant of Moslem’s Decision in Performing Commerce Zakat Payment: Case Study in Malang City, East Java Province

Abstract: Zakat has known as one of the vital instrument in economic that holds some benefits for increasing aggregate demand, expanding job opportunities, reducing poverty and triggering economic growth. As one of the large cities in East Java Province, Malang has a potential issue through commerce zakat which most of the people's livelihood engaged to and composition of regional income (PDRB) is dominated by a commerce sector. On the other hand, it is not supported by the real condition in the field that shows the opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
(4 reference statements)
0
9
1
1
Order By: Relevance
“…This study is different with previous research by Merlinda, et al, because this study uses awareness of profession zakat as the dependent variable, while previous research by Merlinda, et al, (2016) uses the zakat commerce variable. We also expands the scope of the sample, throughout Indonesia, This study also adds an accessibility variable, which was previously used in Gurning and Ritonga's (2015) research to explain its relationship with zakat awareness in general.…”
Section: Previous Research By Abucontrasting
confidence: 58%
See 2 more Smart Citations
“…This study is different with previous research by Merlinda, et al, because this study uses awareness of profession zakat as the dependent variable, while previous research by Merlinda, et al, (2016) uses the zakat commerce variable. We also expands the scope of the sample, throughout Indonesia, This study also adds an accessibility variable, which was previously used in Gurning and Ritonga's (2015) research to explain its relationship with zakat awareness in general.…”
Section: Previous Research By Abucontrasting
confidence: 58%
“…Istiqomah and Asrori (2019) explains that the level of literacy, accountability, and transparency of the zakah positive effect on confidence muzakki to the institution of zakah collection. Merlinda, Burhan, and Ekawaty (2016) in his research on the factors that influence the decision to pay zakah commerce concluded that the decision to pay zakah strongly influenced by income and knowledge of her about charity. Furthermore, Merlinda et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore topics about paying zakat was researched by Pangestu and Jayanto, 2017;Ridlwan and Sukmana, 2017;Doktoralina and Bahari, 2017;Nasution, 2017;Nur, 2018;Sejati et al, 2018;Wahid et al, 2004;Norulazidah, 2008;Wahid et al, 2007;Bachmid et al, 2012;Harahab, 2016;Huda and Gofur, 2012a;Huda et al, 2012b;Merlinda et al, 2016;Mustafa et al, 2013;Putra, 2016;Abbas et al, 2018.…”
Section: Development Of Main Topics Of Zakah Research Discussionmentioning
confidence: 99%
“…Kemudian dalam riset yang dilakukan oleh Abu Bakar dan Rashid (2010), Indahsari (2013) dan Majid (2017), memperkuat temuan bahwa Muzakki mempertimbangkan tingkat kepuasan dan kepercayaan diri sebagai preferensi dalam membayar zakat.Kemudian temuan lain yang diungkapkan dalam riset Firdaus et al (2012) dan Indahsari (2013) mendapatkan bahwa tingkat pendapatan dan pekerjaan juga memengaruhi Muzakki dalam membayar zakat. Selain itu, ada faktor lain yang diungkapkan oleh Dahlan (2008), Huda et al (2014), Merlinda et al (2016) dan Majid (2017) Zainal et al (2016).Temuan lain dalam mengungkap faktor perspektif lembaga adalah terkait dengan persepsi kualitas layanan seperti yang diungkapkan dalam riset yang dilakukan Jaelani (2008) dan Zainal (2016). Kemudian adalah persepsi sosialisasi lembaga juga turut menjadi referensi Muzakki dalam memilih Lembaga Zakat seperti yang disimpulkan oleh Dahlan (2008) dan Jaelani (2008).…”
Section: Pendahuluanunclassified